Myasthenia gravis during pregnancy: what care should be taken? - Renata Dal-Prá Ducci; Cláudia Suemi Kamoi Kay; Otto Jesus Hernandez Fustes; Lineu Cesar Werneck; Paulo José Lorenzoni; Rosana Herminia Scola (Arquivos de Neuro-Psiquiatria, 2021)
Abstract Myasthenia gravis (MG) is an autoimmune disease in which the peak incidence is among women of childbearing age. For this reason, there is an overlap between the occurrence of this disease and pregnancy. It is known that MG symptoms can worsen during pregnancy and postpartum, and that pregnancy has special characteristics in MG patients. Children born to myasthenic mothers are at risk of having transient neonatal myasthenia. We briefly review the main relationships between MG and pregnancy, and we make recommendations for MG therapy, pregnancy, delivery, breastfeeding and newborns.